Neural conversational QA: Learning to reason vs exploiting patterns - Verma N.; Sharma A.; Madan D.; Contractor D.; Kumar H.; Joshi S. (My University, 2025)
Neural Conversational QA tasks like ShARC require systems to answer questions based on the contents of a given passage. On studying recent state-of-the-art models on the ShARC QA task, we found indications that the models learn spurious clues/patterns in the dataset. Furthermore, we show that a heuristic-based program designed to exploit these patterns can have performance comparable to that of the neural models. In this paper we share our findings about four types of patterns found in the ShARC corpus and describe how neural models exploit them. Motivated by the aforementioned findings, we create and share a modified dataset that has fewer spurious patterns, consequently allowing models to learn better. © 2020 Association for Computational Linguistics.